2000
DOI: 10.1071/ar99111
|View full text |Cite
|
Sign up to set email alerts
|

Pea yield decline syndrome in South Australia: the role of diseases and the impact of agronomic practices

Abstract: Sixty commercial pea crops were surveyed in 1995 to determine the causes of declining yields. Blackspot (Mycosphaerella pinodes and Phoma medicaginis var. pinodella) and downy mildew (Peronospora viciae) were prevalent in most crops and were identified as probable major contributors to the syndrome. Short rotation intervals (<5 years) between pea crops in paddocks were correlated with increased levels of blackspot and lower grain yields. Early sowing dates were correlated with increased levels of blackspot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 15 publications
1
25
0
4
Order By: Relevance
“…In Australian farming systems, rotation interval between pea crops has recently increased from 3 to 5 years, to avoid infection from in situ inoculum. Disease severity was greater in crops sown on shorter rotations compared to those on longer rotations and yield, based on grower data, was consistently lower in the shorter rotation crops (Davidson and Ramsey 2000). Bretag et al (2001) monitored changes in populations of soil-borne ascochyta blight fungi, following different cropping sequences of field pea and barley.…”
Section: Soil Borne Inoculum and Crop Rotationmentioning
confidence: 98%
See 1 more Smart Citation
“…In Australian farming systems, rotation interval between pea crops has recently increased from 3 to 5 years, to avoid infection from in situ inoculum. Disease severity was greater in crops sown on shorter rotations compared to those on longer rotations and yield, based on grower data, was consistently lower in the shorter rotation crops (Davidson and Ramsey 2000). Bretag et al (2001) monitored changes in populations of soil-borne ascochyta blight fungi, following different cropping sequences of field pea and barley.…”
Section: Soil Borne Inoculum and Crop Rotationmentioning
confidence: 98%
“…In Australia, pea crops are sown two to three weeks after the agronomic optimum to avoid the peak period of ascospore release which occurs at the beginning of the growing season (Bretag 1991). Earlier sown crops have the most ascochyta and the highest percentage of infected grain at harvest particularly in the most intense pea cropping areas (Davidson and Ramsey 2000). In higher rainfall areas later planting has less impact on yield (Davidson and Ramsey 2000), but this practice risks yield loss in short growing seasons and regions where spring rain is limiting, with losses as high as 40% in some later-sown crops .…”
Section: Sowing Datementioning
confidence: 99%
“…Alma). The major control strategy recommended from this research was to delay sowing 4-6 weeks beyond the first autumn rains to minimise ascochyta blight infection from airborne ascospores of D. pinodes (Bretag et al 2000;Davidson and Ramsey 2000;Hawthorne et al 2003). McDonald and Peck (2009) found that disease severity was more than halved and grain yield increased 6% by delaying sowing of Alma by 3-4 weeks to mid June.…”
Section: Introductionmentioning
confidence: 97%
“…Ascochyta blight has remained the most common disease affecting South Australian field pea crops (Davidson and Ramsey 2000;Bretag et al 2006). This disease is caused by a complex of fungi, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, where this fungicide has been used for several years (USA, UK, New Zealand) pathogen resistance has developed (Biddle, 2001). In Australia few growers use metalaxyl either because of the perceived high cost or the deleterious effect upon Rhizobium inoculants (Davidson & Ramsey, 2000). Resistant cultivars are regarded as the best means of control.…”
Section: Discussionmentioning
confidence: 99%